2020
DOI: 10.3390/app10238568
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Engineering and Topology Optimization for Weight-Reduction of a Bell-Crank

Abstract: This paper describes a new design method that was developed to achieve an optimal design method for weight reduction of a bell crank, sourced from a Louis Christen Road Racing F1 Sidecar. The method involved reverse engineering to produce a 3D model of the mechanical part. The 3D bell crank model was converted to a finite element (FE) model to characterize the eigenvalues of vibration and responses to excitation using the Lanczos iteration method in Abaqus software. The bell crank part was also tested using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A. M. Sharma et al [4] crank is used in student formula prototypes which was subjected to a Pullrod force of 1650N , a Damper force of 24N and a Fulcrum force 1674N.Their initial design's stress and deformation was 143.09 MPa and 0.038mm while the final design had a stress generation of 491.65MPa and got deformed by 0.117mm.The material was also shifted from Aluminium 7075 T6 to Titanium 6Al-4V Grade 5 which resulted in weight reduction by 54%. A. Pande et al [3] showed that there is a 55.92% weight reduction in the crank but the displacement varied from 0.0024 to 0.0021 mm only and the stress changed from 0.018MPa to 0.02 MPa.. T. Y. Pang et al [5] had their crank subjected to 2609N in Y direction and 460N in X direction. The original and optimized crank stress values varied from 239.3MPa to 199.8 MPa whereas mass increased by 2.6%.…”
Section: Discussion and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. M. Sharma et al [4] crank is used in student formula prototypes which was subjected to a Pullrod force of 1650N , a Damper force of 24N and a Fulcrum force 1674N.Their initial design's stress and deformation was 143.09 MPa and 0.038mm while the final design had a stress generation of 491.65MPa and got deformed by 0.117mm.The material was also shifted from Aluminium 7075 T6 to Titanium 6Al-4V Grade 5 which resulted in weight reduction by 54%. A. Pande et al [3] showed that there is a 55.92% weight reduction in the crank but the displacement varied from 0.0024 to 0.0021 mm only and the stress changed from 0.018MPa to 0.02 MPa.. T. Y. Pang et al [5] had their crank subjected to 2609N in Y direction and 460N in X direction. The original and optimized crank stress values varied from 239.3MPa to 199.8 MPa whereas mass increased by 2.6%.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Abhishek Mahesh Sharma et al [4] focused on determining bell crank dimensions followed by static structural analysis and optimization of Formula Student Bell Crank along with change in material from Aluminium 7075 to Titanium 6Al-4V Grade 5. T. Y. Pang et al [5] concentrated on the reverse engineering of bell crank on the basis of its natural frequency. They validated their FEA modal analysis experimentally using a laser vibrometer, manufactured their crank, and assembled it in their vehicle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The car's suspension system plays a crucial role in ensuring ride comfort, steering stability, and optimal wheel motion characteristics, particularly when encountering changing road conditions or varying loads. In the context of TO, Pang and Toh Yen [6] proposed an upgraded design for LW racing arms, while Bin ab Razak et al [7] explored the application of TO in the development of additional lightweight racing cars. These studies contribute to the advancement of lightweight design and optimization techniques for racing vehicles, ultimately improving their overall performance and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, fatigue failure is also considered in this study because it is an important design consideration that ensures the durability of a mechanical structure. Recently, FE-SAFE is increasingly being used to estimate the Although various optimization approaches have been adopted by researchers to obtain optimal geometry of a structural component to reduce system weight and power consumption [10][11][12][13], the literature available on the design aspect of the shredder system is limited and only discusses the static and modal analysis [14][15][16][17][18][19]. Various structural topology optimization methods have been adopted by researchers to improve the material distribution of engineering structures [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%